Effects of tillage systems and intercropping of soybean and corn on soil-inhabiting arthropods - Cividanes, Francisco Jorge (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this study was to evaluate the effects of no-tillage and strip intercropping of soybean [Glycine max (L.) Merrill] and corn (Zea mays L.) on the abundance of soil-inhabiting arthropods. The plots were arranged in a randomized complete block design for a 3 by 2 factorial experiment (soybean monoculture, corn monoculture, strip intercropping of soybean-corn x no-tillage, conventional tillage). Each treatment was replicated four times. The arthropods were sampled by pitfall traps during 1996 – 1998. Statistically significant results from at least one season indicated that no-tillage was favorable to predators like ants (Brachymyrmex sp., Camponotus spp. and Ectatomma sp.), carabids (Metius sp.) and Araneae (Lycosidae). Strip intercropping increased the number of Acrididae, while the presence of corn was favorable to the occurrence of Dermaptera in strip intercropping of soybean and corn.